Nutritional ingredient by-product of the pistachio oil industry: physicochemical characterization - Salinas, María Victoria (2021)
Pistachio flour obtained from oil industry was nutritionally characterized for use as food ingredient in functional foods. Proximal composition, jointly with mineral content, amino acids and fatty acid profile were studied. In addition, different components present in this food ingredient have been analyzed by attenuated total reflectance Fourier transform infrared spectroscopy and thermal properties of proteins were evaluated by differential scanning calorimetry. This flour presented high mineral content such as potassium, phosphorus, magnesium and calcium. Moreover, high amount of unsaturated fatty acids, mainly oleic and linoleic were found. Secondary structure of proteins mainly was formed by parallel β-sheet and α-helix. In the by-product, pistachio protein is in a native state and is able to be denatured at temperatures higher than 100 °C. Therefore, food processing of this ingredient can affect the structure of components.